2021
DOI: 10.1200/jco.2021.39.15_suppl.6006
|View full text |Cite
|
Sign up to set email alerts
|

Association of pathological response to neoadjuvant pembrolizumab with tumor PD-L1 expression and high disease-free survival (DFS) in patients with resectable, local-regionally advanced, head and neck squamous cell carcinoma (HNSCC).

Abstract: 6006 Background: Patients with resected HNSCC, with high-risk (positive margins, extracapsular spread [ECE]) or intermediate-risk pathological features have an estimated 1-year DFS of 65% and 69%, respectively. Immune checkpoint blockade improved survival of patients with recurrent/metastatic HNSCC, and preclinical models indicate radiotherapy (RT) synergizes with anti-PD-1. Therefore, we administered the PD-1 inhibitor pembrolizumab (pembro) pre- and post-surgery with adjuvant RT +/- cisplatin in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Updated results of a phase II neoadjuvant pembrolizumab trial prior to surgery followed by adjuvant concurrent pembrolizumab and radiation along with cisplatin for clinically high-risk (T3/4 stage and/or ≥ 2+ LNs) HPV-negative HNSCC patients (NCT02641093) were recently presented (74). This is multi-institutional trial enrolled 92 patients and 76 patients were evaluable for DFS.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated results of a phase II neoadjuvant pembrolizumab trial prior to surgery followed by adjuvant concurrent pembrolizumab and radiation along with cisplatin for clinically high-risk (T3/4 stage and/or ≥ 2+ LNs) HPV-negative HNSCC patients (NCT02641093) were recently presented (74). This is multi-institutional trial enrolled 92 patients and 76 patients were evaluable for DFS.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…This is multi-institutional trial enrolled 92 patients and 76 patients were evaluable for DFS. They used pathological response (PR) criteria which was defined tumor necrosis and/or histiocytic inflammation and giant cell reaction to keratinaceous debris (74). Of eighty evaluated patients, 32 patients (40%) showed a PR [26 partial PR (≥ 20% and <90%) and 6 with major PR (>90%)].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…[13 ▪ ], Wise-Draper et al . [18 ▪▪ ] and Schoenfeld et al . [19 ▪ ]); four trials reported percentage of residual viable tumour areas (Ferris et al .…”
Section: Introductionmentioning
confidence: 95%
“…[13 ▪ ] and Wise-Draper et al . [18 ▪▪ ], adjuvant treatment was heterogenous and included pembrolizumab, radiation therapy and/or chemotherapy for patients with highrisk disease, defined as positive surgical margins and/ or extranodal extension (Table 1). pTR was associated with relapse-free survival (RFS) in the trial by Zuur et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation